THE USE OF FACEBOOK PAGES FOR ENGLISH TEACHERS’ PROFESSIONAL DEVELOPMENT - Sa’adah Ramadhiyah (Proceedings Education and Language International Conference, 2017)
Some teachers find they have limited chance to do formal professional development program such as classroom observation, classroom research, and even training program to improve their knowledge and skill in teaching. However, teachers nowadays look for the information from the internet for their professional development, like Facebook pages for ELT. Teachers use it as an alternative source to improve their professionalism. This present study investigated about advantages of using Facebook pages for English teachers’ professional development. Quantitative method was conducted by the researcher in this study. Moreover, 35 English teachers were selected purposively. They were given a questionnaire and some open-ended questions. The results show that English teachers got many advantages from Facebook pages, such as for their overall professional development as English teachers, their practice in classroom and their collaboration with others. That is why; teachers should be selective in choosing Facebook pages to be followed and filtered the material they adapt from this page.Keywords: Professional development, English teachers, English language teaching, Facebook pages.